2009
DOI: 10.1108/02686900910994791
|View full text |Cite
|
Sign up to set email alerts
|

Usage of Internal Auditing Standards by companies in the United States and select European countries

Abstract: Purpose -The purpose of this paper is to investigate differences in the degree of usage and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 7 publications
4
19
0
Order By: Relevance
“…They believe that variations in the results of some previous studies related to the practice of internal audit can only be explained by the differences in contextual factors arising from the environments in which they were conducted and they encourage research on the internal audit effectiveness in different corporate governance contexts in order to promote the importance of the profession in contemporary organisational settings. The results of research conducted by Burnaby, Abdolmohammadi, Hass, Sarens, and Allegrini (2009) support that view, according to which there is a difference in the application of Standards between countries in Europe and the US, and the research of Sarens and Abdolmohammadi (2011) showed that the cultural differences between the countries are associated with the level of compliance and implementation of Standards.…”
Section: Measurement Of Internal Audit Effectivenesssupporting
confidence: 50%
See 1 more Smart Citation
“…They believe that variations in the results of some previous studies related to the practice of internal audit can only be explained by the differences in contextual factors arising from the environments in which they were conducted and they encourage research on the internal audit effectiveness in different corporate governance contexts in order to promote the importance of the profession in contemporary organisational settings. The results of research conducted by Burnaby, Abdolmohammadi, Hass, Sarens, and Allegrini (2009) support that view, according to which there is a difference in the application of Standards between countries in Europe and the US, and the research of Sarens and Abdolmohammadi (2011) showed that the cultural differences between the countries are associated with the level of compliance and implementation of Standards.…”
Section: Measurement Of Internal Audit Effectivenesssupporting
confidence: 50%
“…Sarens (2009, p. 3) refers to the importance of research regarding the internal audit effectiveness and its impact on corporate governance, stressing that one can consider the internal audit to be effective only when its activity has a positive impact on the quality of corporate governance. His conclusion is based on considerations of Gramling, Maletta, Schneider, and Church (2004, p. 194-196), who considered internal audit as one of the 'corporate governance cornerstones' .…”
Section: Introductionmentioning
confidence: 99%
“…The view in these circumstances is that complementary and substitution effects are possible between the committee and the IAF (Barua et al, 2010). Other research has discussed internal audit conformance with the ISPPIA (Sarens and Abdolmohammadi, 2011a;Abdolmohammadi, 2009;Marais et al, 2009). For instance, found that the size of The current issue and full text archive of this journal is available on Emerald Insight at: www.emeraldinsight.com/0268-6902.htm Influence of audit committees the IAF affects the usage of the ISPPIA in the USA and Italy.…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, internal audit conformance with the ISPPIA is discussed in several studies (Sarens and Abdolmohammadi, 2011a;Abdolmohammadi, 2009;Leung and Cooper, 2009;Marais et al, 2009). For example, Abdolmohammadi (2009), researching in Anglo-Saxon countries, found that 13.5 per cent of chief audit executives (CAEs) did not use these standards, and that many who used them showed poor conformance with particular directives.…”
mentioning
confidence: 99%
“…This study is important because very little work has been reported in the literature to investigate the level of use of Standards and compliance with them. Burnaby et al (2008) provide data on the usage of Standards in the United States and a select group of countries in Europe (Belgium, Italy, Netherlands, and the UK/Ireland). Their descriptive study identifies significant minorities of internal auditors who do not use or comply with Standards .…”
Section: Introductionmentioning
confidence: 99%